PENEGAKAN HUKUM TERHADAP TINDAK PIDANA MEMPERJUALBELIKAN VIDEO COMPACT DISC PORNO BERDASARKAN PASAL 29 UNDANG-UNDANG NOMOR 44 TAHUN 2009 TENTANG PORNOGRAFI - Ira Rahayu; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Crime in the field of pornography is one of the fast growing criminal activity due to the developments in technology and information. Various things have been done to reduce the occurrence of criminal acts in the field of brands ranging from the establishment of Law No.44 Year 2008 on Pornography. However, in the field of pornography is a crime still existed in society, even predictable crimes against counterfeiting in this brand though it was addressed, will continue to increase.Based on these reasons underlying the author's interest to write a thesis with issues such how law enforcement in criminal acts memperjualbelikan compatc video disc / VCD porn under article 29 of Law No. 44 of 2008 concerning the setting pornography. This thesis is empirical juridical case studies jurisdictions Pekanbaru City Police Sector. In Indonesia alone, the problem of pornography is not new. Where in the Criminal Code concerning pornography has been set in Article 281, 282, 283, and Article 533 of the Criminal Code. Besides the problem of Pornography also set in the Broadcasting Law, the Law of Film, Press Law, the Telecommunications Act, Act ITE. However, because the Indonesian government feels that the existing provisions in the Act that have been there was less strong binding of the perpetrators, the government then sought a ban on pornography that has been set out in a regulation of pornography, namely Law No. 44 Year 2008 on Pornography. Regarding the implementation of Law No. 44 Year 2008 on Pornography against the seller VCD / DVD porn must be fulfilled principal elements contained in the indictment that charged by the public prosecutor.Keywords: Pornography Crime-Crime-Video Compatc Disc / VCD